(untitled) (Global Media Journal - German Edition, 2015)
The impact of place and locality in narrative media can be regarded as seminal for the medium’s function of communicating culture and negotiating societal discourses. As a result of the growing attention in globalisation theory and transnational considerations, space and place have become key issues to understanding the circulation of cultural commodities within an increasingly global and supra-national context. Taking the case of two popular contemporary European crime series, the German series Tatort and the Danish/Swedish series Bron//Broen, our aim is to focus on and carve out local colour as an aesthetic textual strategy, as well as relate it to a production context and to a broader discussion of the region/nation and the transnational/global. We argue that local colour can be located at three different levels: Firstly, on the level of representation as part of an overall narrative and aesthetic strategy that produces structures of appeal for the audiences. Secondly, within the frame of production, public broadcasting service, and policy that stage the general preconditions of cultural products. Thirdly, we regard locality as commodity and cultural consumption (e.g. branding, tourism, investments). Local colour and the representation of places evoke different concepts of imagined communities related to the regional and the national, but also the global and transnational.